Persepsi Pasien Terhadap Mutu Pelayanan Keperawatan Di Instalasi Rawat Inap Rumah Sakit Umum Daerah Anuntaloko Parigi Kabupaten Sigi - Yanriatuti, Ida; Susanto, Denny; Kantohe, Imelda; Parmi (BULLET : Jurnal Multidisiplin Ilmu, 2024)
Nursing services are an integral part of health services in hospitals which have a role in achieving efficiency and the quality of the hospital's image in the community. Nurses are one of the professional staff, so it is necessary to improve the quality of hospital nursing care services. As a result of interviews conducted by researchers, 10 patients said that the service provided was quite good and satisfactory, but 3 patients said they were not satisfied with the service provided, and were less responsive to complaints from patients being treated in the room. This research aims to determine patient perceptions of the quality of nursing services in the inpatient installation room at the Torabelo Regional General Hospital, Sigi Regency. This type of research uses a descriptive research design method, in the inpatient installation of the Tora Belo General Hospital, Sigi Regency. Pine Room, Ebony. Data collection uses questionnaires. The variable in this research is the patient's perception of the quality of nursing services. Data analysis uses univariate analysis. The population in this study were all hospitalized patients with a total sample of 44 people using proportional sampling by accidental sampling which met the inclusion and exclusion criteria. The results of research on patient perceptions of the quality of nursing services in the inpatient installation room at the Tora Belo Regional General Hospital, Sigi Regency showed that of the 44 respondents, there were more patients who had a good perception, namely 23 (52.3%) while patients who had a less good perception were 21 (47,7%). Based on the research results, it can be concluded that the majority of respondents have a good perception of the quality of nursing services at Tora Belo General Hospital, Sigi Regency. It is hoped that the Tora Belo General Hospital can further improve the quality of nursing and health services through training programs or health seminars.